2023
DOI: 10.3390/photonics10040464
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Impact of Ultraviolet B Radiation on Oral Healthy and Tumor Cells

Abstract: Ultraviolet radiation (UVR) is generally considered a primary tumorigenic agent. While UVR exposure has been studied, especially at the skin level, the impact of UV exposure on internal tissues and its effect on the appearance and the development of tumors has not yet been fully examined. Although there are maximum limits for UVR exposure on external tissues, other internal tissues, such as oral tissue, can be exposed to UVR as well. Over the course of diagnosis and treatment, oral cells may be exposed to ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…After 5-10 min in the dark at room temperature, the staining solution was removed and the cells were washed three times with PBS. Apoptosis was quantified by calculating the apoptotic index, applying the formula described in the study reported by Gag and co-workers [64]. To take fluorescent images at a magnification of 10×, the fluorescence inverted microscope Olympus IX73 (Olympus, Tokyo, Japan) was used.…”
Section: Nuclear Staining Evaluationmentioning
confidence: 99%
“…After 5-10 min in the dark at room temperature, the staining solution was removed and the cells were washed three times with PBS. Apoptosis was quantified by calculating the apoptotic index, applying the formula described in the study reported by Gag and co-workers [64]. To take fluorescent images at a magnification of 10×, the fluorescence inverted microscope Olympus IX73 (Olympus, Tokyo, Japan) was used.…”
Section: Nuclear Staining Evaluationmentioning
confidence: 99%
“…The cell viability was assessed at the end of a 24 h treatment with RUT, OA, LA, RUT-O and RUT-L (25, 50, 100, 125 µM) by performing the MTT test according to the following steps: (i) the cells' seeding in flat-bottom 96-well plates at a density of 10 4 cells/well; (ii) the cells' treatment with the investigated compounds; (iii) the addition of 10 µL MTT reagent in each well and 3 h incubation of the plates at 37 • C and 5% CO 2 ; (iv) the addition of Life 2024, 14, 215 4 of 16 100 µL solubilizing solution and 30 min incubation of the plates at room temperature; and (v) absorbance measurement at 570 and 630 nm. The protocol was followed as also presented by Gag et al [19].…”
Section: Cell Viability Assessment-the Mtt Testmentioning
confidence: 99%
“…The impact of all tested compounds (1, 10, 25, 50, and 100 µM) on the viability of H9c2(2-1), HepaRG, and HaCaT cells was assessed using the MTT method which was performed according to a previous publication [37]. Briefly, the cells cultured in 96-well plates were exposed to SIL, SIL-O, and SIL-L for 24 h. At the end of the treatment, the culture medium containing SIL, SIL-O, and SIL-L was removed and replaced with 100 µL/well of the specific culture media for the used cell lines (DMEM for H9c2(2-1) cells and HaCaT; William's E Medium for HepaRG).…”
Section: Cell Viability Assaymentioning
confidence: 99%